Eurozone Debt Crisis - Sadraddinli, Sabir; Dudzich, Viktar; Tesařová, Žaneta; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2022)
The main goal of this study is to examine the negative impacts that the debt crisis has had on the member nations, as well as the measures that have been implemented in these nations and the EU rules and procedures that will allow for the structural development of these measures. In this regard, the debt crises that developed in some structurally vulnerable EU member countries towards the end of the 2000s had a significant impact on the economies of these countries, while on the other hand, it was amply demonstrated how inadequate the EU's economic management was in the face of the crisis. Without a doubt, the most crucial issue under consideration at this time was what steps the Union's decision-making bodies would take, as opposed to those made by individual member states, to avert a financial crisis. Along with the debt crisis, the report also discusses the procedures created by the European Economic Administration to stop the crisis by enhancing financial discipline and assuring alignment between the national economy and fiscal policy. The research also covers how the member nations are coping with the crisis as well as how the EU institutions are handling it. One of the most divisive and pressing economic crises of recent years, the EU debt crisis is a research topic that appears to take up a lot of time on the economic agenda as a political issue that also raises concerns about the EU's future. This appears to be the case since the EU debt crisis is a study topic that seems to take up a lot of political and economic agenda space. Greece and Italy case studies are presented in the thesis' last section.
Vedoucí práce: Viktar Dudzich
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses